2012
DOI: 10.1007/s00382-012-1547-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal SST-precipitation relationship and its spatial variability over the tropical summer monsoon region

Abstract: International audienceThe SST-precipitation relationship in the intraseasonal variability (ISV) over the Asian monsoon region is examined using recent high quality satellite data and simulations from a state of the art coupled model, the climate forecast system version 2 (CFSv2). CFSv2 demonstrates high skill in reproducing the spatial distribution of the observed climatological mean summer monsoon precipitation along with its interannual variability, a task which has been a conundrum for many recent climate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(73 citation statements)
references
References 57 publications
3
69
0
1
Order By: Relevance
“…The Indian Ocean and monsoon exhibit a coupled relationship 32,42,43 , and it is also possible that a feedback from a weak monsoon accelerates the warming in the Indian Ocean 22 . Some studies have suggested a role for anthropogenic aerosols in weakening the monsoon circulation during the recent decades 40,[44][45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Indian Ocean and monsoon exhibit a coupled relationship 32,42,43 , and it is also possible that a feedback from a weak monsoon accelerates the warming in the Indian Ocean 22 . Some studies have suggested a role for anthropogenic aerosols in weakening the monsoon circulation during the recent decades 40,[44][45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…For the numerical model experiments, we use the standard configuration of a global coupled ocean-atmosphere model, the Climate Forecast System version 2 (CFSv2). The CFSv2 model simulates the mean monsoon and its interannual variability reasonably well, and hence used in this study 42 . The oceanic component has a 0.25-0.5°horizontal resolution, 40 vertical levels and includes an ice model.…”
Section: Methodsmentioning
confidence: 99%
“…For example, several studies (e.g., Fu et al 2003;Roxy and Tanimoto 2007;Roxy et al 2013) attribute the increased low-level convergence to increased shallow convection, which results from enhanced SST-induced convective instability. Some studies suggest a windevaporation feedback (e.g., Marshall et al 2008) whereby increased shortwave fluxes lead to enhanced surface evaporation and low-level convergence, while others (Hsu and Li 2012) suggest that intraseasonal SST gradients themselves can induce modest low-level convergence anomalies according to the ideas of Lindzen and Nigam (1987) and Back and Bretherton (2009).…”
Section: Introductionmentioning
confidence: 98%
“…Among the improvements cited were stronger ISO variability in AGCMs with a weak or nonexistent MJO, reduced ISO variability in AGCMs with excessive variability, more realistic phase speed (either faster or slower than in the AGCM) and wavenumber-frequency spectra, more realistic horizontal and vertical structure of the MJO, better eastward propagation (not always accompanied by better northward propagation during boreal summer), and better northward propagation during boreal summer season (not always accompanied by better eastward propagation). Clearly, there are nuanced modelto-model differences in the nature of improvement due to coupling, and a few studies suggest either that the coupling strength is too strong in some models (Wu et al 2008;Bollasina and Nigam 2009) or that the coupled SST variability can be too high (Roxy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation